2007
DOI: 10.1016/j.jhse.2007.02.206
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Treatment of Persistent Radial Nerve Paralysis Associated with Fractures of the Middle Third of Humerus: Review and Evaluation of the Long-Term Results of 52 Cases

Abstract: This study was undertaken to determine the efficacy of delayed surgical treatment in cases of persistent radial nerve paralysis after fractures of the middle third of the humerus. We have limited this study to patients who had absolutely no functional recovery of the radial nerve 3 to 4 months after middle third humeral fractures. The fractures were treated by a variety of orthopaedic methods, conservative and surgical, in other departments and hospitals. Surgical exploration of the radial nerve was carried ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…By this approach, it is possible to avoid supra-olecranon entry complications [1,3,15,16]. Also, neural problems of dual entry through medial and lateral points could be overcome [19]. Great attention should be paid for such entry and proper opening of the cortex should be done to avoid supracondylar humeral fractures or neural injury.…”
Section: Discussionmentioning
confidence: 99%
“…By this approach, it is possible to avoid supra-olecranon entry complications [1,3,15,16]. Also, neural problems of dual entry through medial and lateral points could be overcome [19]. Great attention should be paid for such entry and proper opening of the cortex should be done to avoid supracondylar humeral fractures or neural injury.…”
Section: Discussionmentioning
confidence: 99%
“…Acta Orthopaedica Belgica, Vol. 87 - 3 -2021 In some studies, the incidence is a little higher with mid-shaft or mid to distal-shaft fractures, and with transverse fractures and spiral fractures compared to oblique and comminuted fractures (3)(4)(8)(9)(13)(14)17).…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, it is generally recommended to identify the radial nerve when plating shaft fractures and there are a number of studies on plating associated with radial neuropathy (3)(4)(5)(6)(7)(8)(9)(10). Considering fixation of HSFs with a long intramedullary nail, there are far fewer publications in English addressing that complication.…”
Section: Introductionmentioning
confidence: 99%
“…There have also been a number of studies that explore the outcomes of radial nerve palsies managed operatively after the failure of initial conservative management, which also generally suggest a positive outcome . In these situations, however, the patient is left uncertain as to the eventual outcome of their palsy.…”
Section: Introductionmentioning
confidence: 99%
“…3 There have also been a number of studies that explore the outcomes of radial nerve palsies managed operatively after the failure of initial conservative management, which also generally suggest a positive outcome. [4][5][6] In these situations, however, the patient is left uncertain as to the eventual outcome of their palsy. The study by Korompilias et al 7 found that at delayed exploration of 12 closed injuries with radial nerve palsy, two had complete transection of the nerve, two were entrapped in the fracture and two were adhesed (and underwent neurolysis), and that all intact nerves recovered 20-24 weeks post injury.…”
Section: Introductionmentioning
confidence: 99%